Comparative postoperative prognosis of ceramic-on-ceramic and ceramic-on-polyethylene for total hip arthroplasty: an updated systematic review and meta-analysis - Wu, Tingyu; Jiang, Yaping; Shi, Weipeng; Wang, Yingzhen; Li, Tao (PeerJ, 2024)
Objective To compare the clinical outcomes between ceramic-on-ceramic (CoC) and ceramic-on-polyethylene (CoP) bearing surfaces in patients undergoing total hip arthroplasty (THA) through a pooled analysis and evidence update. Methods We performed a systematic literature search using PubMed, Embase, Cochrane Library and Web of Science up to March 2023 for studies that compared the bearing surfaces of CoC and CoP in patients undergoing THA. The primary outcomes were the incidence of common postoperative complications and the rate of postoperative revision. The secondary outcome was the Harris Hip Score. Results A total of 10 eligible studies involving 1,946 patients (1.192 CoC-THA versus 906 CoP-THA) were included in the evidence synthesis. Pooled analysis showed no significant difference in the rates of common postoperative complications (dislocation, deep vein thrombosis, infection, wear debris or osteolysis) and of revision. After eliminating heterogeneity, the postoperative Harris Hip Score was higher in the CoC group than in the CoP group. However, the strength of evidence was moderate for the Harris Hip Score. Conclusion CoC articulations are more commonly used in younger, healthier, and more active patients. While the performance of conventional polyethylene is indeed inferior to highly cross-linked polyethylene, there is currently a lack of sufficient research comparing the outcomes between highly cross-linked polyethylene and CoC bearing surfaces. This area should be a focal point for future research, and it is hoped that more relevant articles will emerge. Given the limited number of studies included, the heterogeneity and potential bias of those included in the analysis, orthopaedic surgeons should select a THA material based on their experience and patient-specific factors, and large multicentre clinical trials with >15 years of follow-up are needed to provide more evidence on the optimal bearing surface for initial THA.
Keywords: Ceramic-on-ceramic; Ceramic-on-polyethylene; Total hip arthroplasty; Complications; Revision; Harris hip score